Determination of Early and Late Endothelial Progenitor Cells in Peripheral Circulation and Their Clinical Association with Coronary Artery Disease. (16th September 2015) - Tagawa, Shotoku; Nakanishi, Chiaki; Mori, Masayuki; Yoshimuta, Tsuyoshi; Yoshida, Shohei; Shimojima, Masaya; Yokawa, Junichiro; Kawashiri, Masa-aki; Yamagishi, Masakazu; Hayashi, Kenshi
Abstract : The clinical implications of early and late endothelial progenitor cells (EPCs) in coronary artery disease (CAD) remain unclear. We investigated endothelial dysfunction in CAD by simultaneously examining early and late EPC colony formation and gene expression of specific surface markers in EPCs. EPCs were extracted from a total of 83 subjects with (n = 47 ) and without (n = 36 ) CAD. Early and late EPC colonies were formed from mononuclear cells extracted from peripheral blood. We found that fewer early EPC colonies were produced in the CAD group (7.2 ± 3.l/well) than those in the control group (12.4 ± 1.4/well, p < 0 . 05 ), and more late EPC colonies were produced in the CAD group (0.8 ± 0.2/well) than those in the control group (0.25 ± 0.02/well, p < 0.05 ). In the CAD group, the relative expression of CD31 and KDR of early and late EPCs was lower than in the control group. These results demonstrate that CAD patients could have increased late EPC density and that early and late EPCs in CAD patients exhibited immature endothelial characteristics. We suggest that changes in EPC colony count and gene expression of endothelial markers may have relation with development of CAD.